1993
DOI: 10.1161/01.hyp.22.6.853
|View full text |Cite
|
Sign up to set email alerts
|

Effects of angiotensin II and endothelin-1 on platelet aggregation and cytosolic pH and free Ca2+ concentrations in essential hypertension.

Abstract: The aims of this study were to determine the relations between platelet free calcium concentrations ([Ca 2+ D, intracellular pH (pH,), and aggregation and to assess the effects of angiotensin II (Ang II) and endothelin-1 on these platelet parameters in normotensive subjects and hypertensive patients. Seventeen normotensive subjects, 25 untreated hypertensive patients, and 34 treated hypertensive patients were studied. Platelet cytosolic free [Ca 3+ ]| and pH, were measured spectrofluorometrically using spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
4

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 48 publications
3
38
0
4
Order By: Relevance
“…Physiological concentra- tions of angiotensin II (10-11 mol) were observed to enhance adrenaline-induced platelet aggregation, while a high concentration (10-7 mol) had an inhibitory effect on platelet aggregation (24). Platelet aggregation induced by thrombin was enhanced in the presence of 10_9 mol angiotensin II (25). These findings suggest that the elevation of circulating angiotensin II may induce platelet activation in vivo and ACEI may inhibit platelet activation by reducing circulating angiotensin II.…”
Section: Discussionmentioning
confidence: 85%
“…Physiological concentra- tions of angiotensin II (10-11 mol) were observed to enhance adrenaline-induced platelet aggregation, while a high concentration (10-7 mol) had an inhibitory effect on platelet aggregation (24). Platelet aggregation induced by thrombin was enhanced in the presence of 10_9 mol angiotensin II (25). These findings suggest that the elevation of circulating angiotensin II may induce platelet activation in vivo and ACEI may inhibit platelet activation by reducing circulating angiotensin II.…”
Section: Discussionmentioning
confidence: 85%
“…For example, there is evidence of an increased effect of Ang II on platelet-free calcium concentrations and intracellular pH in untreated hypertensives. 6 Other studies showed that there was an upregulation of AT 1 receptor mRNA in platelets of patients with primary aldosteronism and renovascular hypertension. 26 The number of Ang II binding sites also differs in the platelets of pregnant women with and without hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Human platelets have Ang II receptors (AT 1 ) and this hormone is known to activate platelets. 6 However, Ang II has not previously been shown to induce platelet shape change (PSC), an early phase of platelet activation, which may be associated with the release of intra-platelet growth factors. [7][8][9][10][11][12][13][14][15][16] Inhibiting PSC is important because this is an aspirin-resistant phase of platelet activation.…”
Section: Introductionmentioning
confidence: 99%
“…33 Angiotensin II stimulation significantly increases intracellular platelet calcium concentrations, intracellular pH and thrombin-induced platelet aggregation in untreated hypertensive as well as normotensive individuals. 34 The release of angiotensin II following pro-aggregatory stimulation suggests that this may be one of the mechanisms through which platelets can locally modulate vascular tone and promote atherogenesis. 35 The infusion of angiotensin II increased plasma b-thromboglobulin levels, reflecting a-granule secretion and expression of P-selectin.…”
Section: Discussionmentioning
confidence: 99%